2016
DOI: 10.1186/s13633-016-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Influences of gender on cardiovascular disease risk factors in adolescents with and without type 1 diabetes

Abstract: BackgroundWomen with type 1 diabetes (T1D) have a four-fold increased risk for cardiovascular disease (CVD) compared to non-diabetic (non-DM) women, as opposed to double the risk in T1D men compared to non-DM men. It is unclear how early in life CVD risk differences begin in T1D females. Therefore, our objective was to compare CVD risk factors in adolescents with and without T1D to determine the effects of gender on CVD risk factors.MethodsThe study included 300 subjects with T1D (age 15.4±2.1 years, 50 % male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
(38 reference statements)
3
22
0
1
Order By: Relevance
“…To minimize cardiometabolic risk, an intensive approach to weight management should be considered for girls with T1D who are overweight or obese during pre‐adolescence, taking into account the complex relationship with glycemic control and insulin omission as noted above. The significant differences by sex in the overall HbA1c trajectory group model (Table ), and, in the multinomial logistic regression (Table ), are consistent with a previous cross‐sectional study of sex differences in HbA1c and BMI z‐score …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To minimize cardiometabolic risk, an intensive approach to weight management should be considered for girls with T1D who are overweight or obese during pre‐adolescence, taking into account the complex relationship with glycemic control and insulin omission as noted above. The significant differences by sex in the overall HbA1c trajectory group model (Table ), and, in the multinomial logistic regression (Table ), are consistent with a previous cross‐sectional study of sex differences in HbA1c and BMI z‐score …”
Section: Discussionsupporting
confidence: 88%
“…Most children and adolescents with type 1 diabetes (T1D) in the United States (US) do not meet the recommended hemoglobin A1c (HbA1c) target of <7.5% (58 mmol/mol), which increases their risk of developing diabetes‐related complications . Recent studies have reported that girls with T1D have worse metabolic control and complications than boys with T1D, and higher body mass index (BMI) z‐scores than boys with T1D and girls without T1D . Women with T1D have a significantly higher relative risk of cardiovascular disease (CVD) compared to men with T1D, when each are compared to their non‐diabetic counterparts .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the percentage of participants with dyslipidaemic LDL and non‐HDL cholesterol levels was lower in the pump treatment group compared to the injection therapy group. In addition, it also confirmed well‐established associations of elevated lipid level, and more specifically LDL and non‐HDL cholesterol level, with female sex, age, diabetes duration, HbA 1c and BMI . The percentage of participants with an LDL cholesterol level ≥2.6 mmol/l was slightly higher (38%) than reported in other Type 1 diabetes cohorts (35% and 34.5% in studies from the USA and Norway, respectively) .…”
Section: Discussionsupporting
confidence: 80%
“…In that study, the presence of type 1 diabetes was greatly associated with prevalence of coronary calcification in women compared to men despite similar glycemic control and higher lipids detected in men (29). Studies have reported higher HbA1c, BMI Z-scores, atherogenic lipoprotein subfractions, and insulin resistance in adolescent girls with type 1 diabetes compared to adolescent boys with the condition (30,31). Taken together, gender differences in glycemic control, BMI, or insulin resistance earlier in life (childhood and adolescence) may result in bad metabolic memory and a higher risk for cardiovascular diseases in women with type 1 diabetes as they transition to adulthood.…”
Section: Accepted Manuscriptmentioning
confidence: 82%